ENVIRONMENTAL INFLUENCERS ON INSTAGRAM: CONNECTIONS AND FRICTIONS BETWEEN ACTIVISM, LIFESTYLES AND CONSUMPTION. - San Cornelio, Gemma; Ardèvol, Elisenda; Martorell, Sandra (AoIR Selected Papers of Internet Research, 2021)
Environmental crisis is one of the main issues on the current social, political and media agenda that has spread to citizens engaging environmental activism in many ways. This paper focuses on the emergence of a very specific type of environmental activism in social media that we named as “eco-influencers”. Drawing on our findings of an ongoing digital ethnography (Pink et al. 2016; Hjorth, Horst, Galloway, Bell, 2017) among Instagram profiles devoted to disseminate contents related to sustainability and climate change, our aim here is to explore some controversial issues regarding how they understand independence in relation to activism, lifestyle, consumption and work. We named these environmental activist eco-influencers as these profiles develop similar strategies as those that, according to Leaver, Hihghfield and Abidin as influencers are characterized by: 1) applying positive self-branding strategies, 2) managing their visibility 3) cultivating their community of followers adopting storytelling techniques consistent with their lifestyles (Leaver, Hihghfield, Abidin, 2020: 106). The fieldwork consists in participant observation in Instagram since July 2020 following the profiles through a collective research account to maintain interaction and expand our field site until we have an intentional sample of 60 profiles that allowed us to create a first typology and beginning in-depth interviews. In this paper we highlight some features that have been raised regarding their activity as activists and the very notion of “eco-influencer”.